Hospitalizations for Mental Health in Migrants and Italian Citizens in the Marche Region Between 2011 and 2023: a Population-Based Study Using Healthcare Utilization Databases (Mighty Project P2022asxkr) (Epidemiology, Biostatistics, and Public Health, 2025)
IntroductionInternational migration is considered a complex and unstoppable phenomenon. Migrant population is a heterogeneous group of people who experience migration for different reasons and that are considered to be at increased risk of developing mental disorders [1]. Scientific evidence on migrants’ mental health is limited, as is knowledge of their access to and use of specific care services and treatments. As compared to natives, higher rates of involuntary hospitalization were found among migrants in most European countries [1,2].AimThe aim of the present study was to compare mental health hospitalization rates in Migrants and Italians in Marche Region during 2011-2023, and to investigate their differences according to demographic and clinical characteristics.MethodsA cross-sectional population-based study on individuals hospitalized in psychiatric departments of all ages and resident in Marche Region in the period between 2011 and 2023 was conducted, using healthcare utilization databases (Hospital Discharge and Regional Beneficiaries databases). Residents were divided into Migrants from High Migratory Pressure Country (HMPC) and Italians, according to citizenship [3].The primary diagnosis field of hospital discharge database was used to estimate the prevalence of different types of mental disorder using ICD-9 CM codes (290.*-319.*).Annual age-standardized hospitalization rates were calculated for HMPC Migrants and Italians using the 2019 Italian population [4] as standard, using the direct method. Rates were stratified by sex and the Standardized Rate Ratios (SRR) with 95% Confidence Interval (95%CI) were calculated by sex and year of observations as ratio between HMPC and Italian rates. All data were processed in compliance with the European (GDPR, EU 2016/679) and national privacy laws (D.lgs. 196/2003 and subsequent amendments). ResultsA total of 59.881 hospitalizations were analyzed, 93.3% of which were of Italians. The mean age was higher in Italians than in HMPC (43.8 y versus 32.2 y). In both populations, hospitalizations most frequently referred to unmarried individuals (62% in Italians, 64% in HMPC) and to individuals with the lowest level of education (45% in Italians, 48% in HMPC).Hospitalizations originated mainly from Emergency Departments admissions (25.4% Italians, 28.8% HMPC), medical indications (24.8% Italians 20.4% HMPC), prison (13.4% Italians, 13.7% HMPC) or hospitalization at the time of delivery (13.3% Italians 11.4% HMPC).The most frequent diagnoses were schizophrenia and other functional psychosis (29.6% in Italians vs 31.6% HMPC), alcoholism and toxicomania (15.2% in Italians vs 21.7% HMPC) in both populations. Hospitalizations for depression in Italians and HMPC had similar proportions (11.1% vs 11.2%, respectively) but the frequency was more than twice as high in HMPC women as in HMPC men (8.3% vs 2.9%); the proportions of hospitalizations for mania and bipolar affective disorders hospitalizations were higher in HMPC women than in HMPC men (7.0% vs 2.1%); alcoholism and toxicomania were more frequent in HMPC women than in Italian women (11.5% vs 4.8%), and also than in HMPC men (11.5% vs 10.1%).Excluding the 2020-2021 (the pandemic period) in which the lowest rates were recorded (2.5-2.5 and 2.3-2.0 for Italians men and women respectively, 1.4-1.7 and 1.6-2.2 for HMPC men and women respectively), the standardized rates (x1000 residents) of hospitalization ranged between 1.7 to 2.6 (in 2023 and 2019, respectively) for HMPC men and between 1.8 to 2.5 (in 2023 and 2017, respectively) for HMPC women; in Italians, rates ranged between 2.6 to 4.2 (2023 and 2011/2012, respectively) for men and between 2.1 to 3.5 (in 2023 and 2011, respectively) for women.Standardized rate ratios (Figure 1) showed that HMPC reported lower hospitalizations for mental disorders than Italians over the entire study period for both genders. In females, the differences between the two populations were less pronounced than in males.ConclusionThis study based on healthcare utilization databases allowed to quantify the use of inpatient psychiatric care in both Migrants and Italians in the Marche Region.Our results showed a lower rate of hospitalization for mental disorders in Migrants than in Italians over the study period, with differences by gender and by type of mental disorder.Considering that mental disorders are characterized by chronicity, diagnostic-therapeutic difficulties and strong family and social impact, further assessments are needed to identify the reasons for the use of hospitalization versus community-based care services in both populations.